Pendidikan Habituasi Ibadah Anak: Menelusuri Validitas dan Menangkap Pesan Hadits Perintah Shalat Anak - Amrulloh, Amrulloh (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2016)
Abstract This paper discusses the message and examines the validity of Hadith commanding prayer for children who have not attained the age of puberty (baligh). Prayer for early children is extremely important for the parents or guardians to bear in mind, so they are accustomed to and do not feel as burden when they are in adulthood. Hence, through hadith the Prophet ordered the parents or whoever is responsible to order their children to perform prayers since the age which is actually still fairly early. However, the Hadith under discussion seems to be less synchronized with the concept of mukalaf and puberty in Islam, and also it highlights physical harassment that is considered irrelevant to the spirit of modern education. After examining the validity of the hadith by utilizing mustalah hadith, such as takhrij and jarh wa ta‘dil, and by analyzing the main message of the hadith tradition by utilizing relevant psychological approach, this paper proves that the hadith of prayer command is not contradictory with the concept of mukalaf and puberty, so relevant to the spirit of modern education